2017
DOI: 10.3892/or.2017.5416
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs act as regulators of cell autophagy in diseases

Abstract: Identification of long non-coding RNAs (lncRNAs) has provided a substantial increase in our understanding of the non-coding transcriptome. Studies have revealed a crucial function of lncRNAs in the modulation of cell autophagy in vitro and in vivo, further contributing to the hallmarks of disease phenotypes. These findings have profoundly altered our understanding of disease pathobiology, and may lead to the emergence of new biological concepts underlying autophagy-associated diseases, such as the carcinomas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 70 publications
2
53
0
Order By: Relevance
“…Consequently, lncRNAs are considered as platforms to perform multiple functions in the cell and they act either in cis or in trans . They are involved in chromatin remodeling, transcriptional co-activation and co-repression, protein inhibition, post-transcriptional modifications (splicing), decoy binding platforms, mRNA stabilization, and more recently in nuclear organization of multichromosomal regions [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Among these functions, lncRNAs bind to chromatin-modifying proteins for their recruitment to specific sites in the genome, and lncRNAs act as competing endogenous RNAs (ceRNAs) for miRNAs.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Consequently, lncRNAs are considered as platforms to perform multiple functions in the cell and they act either in cis or in trans . They are involved in chromatin remodeling, transcriptional co-activation and co-repression, protein inhibition, post-transcriptional modifications (splicing), decoy binding platforms, mRNA stabilization, and more recently in nuclear organization of multichromosomal regions [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Among these functions, lncRNAs bind to chromatin-modifying proteins for their recruitment to specific sites in the genome, and lncRNAs act as competing endogenous RNAs (ceRNAs) for miRNAs.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Long non-coding RNA (lncRNA) is a type of non-coding RNA which is >200 nucleotides in length (9). Previous research has demonstrated that lncRNAs serve diverse functions in cellular processes and are involved in tumorigenesis, progression and metastasis (10,11). However, only a few lncRNAs involved in the development of LUAD have been identified, including histocompatibility leukocyte antigen complex P5, chromatin-associated RNA 10 and metastasis-associated lung adenocarcinoma transcript 1 (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA-miRNA axis was involved in many cellular processes, such as cell development, proliferation, and cell autophagy through controlling gene expression patterns. 22 It has been reported that miR-188-3p participated in the regulation of ATG7 expression and lncRNA autophagy promoting factor (APF) participated in the autophagy regulation by directly binding to miR-188-3p in vivo and vitro. 23 However, whether lncRNA PTPRG-AS1 is involved in cell growth and autophagy by sponging microRNA-185-5p (miR-185-5p) in glioma needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%